Market, state, and community : theoretical foundations of market socialism - Miller, David, 1946- (Oxford University Press, 1990)
In this book, David Miller makes a comprehensive analysis of an economy in which market mechanisms retain a central role, but in which capitalist patterns of ownership have been superceded. He provides a clear, coherent statement of the theoretical basis of market socialism, and justifies it as a viable political option. Through this, he presents an alternative to both New Right and Socialist views.